IMPROVED GROWTH AND COLCHICINE CONCENTRATION IN GLORIOSA SUPERBA ON MYCORRHIZAL INOCULATION SUPPLEMENTED WITH PHOSPHORUS-FERTILIZER - Pandey, Devendra Kumar; Dubey, Rekha Pandey; Malik, Tabarak; Singh, Joginder; Dey, Abhijit (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Gloriosa superba produces an array of alkaloids including colchicine, a compound of interest in the treatment of various diseases. The tuber of Gloriosa superba is a rich source of colchicine which has shown anti-gout, anti-inflammatory, and anti-tumor activity. However, this promising compound remains expensive and Gloriosa superba is such a good source in global scale. Increase in yield of naturally occurring colchicine is an important area of investigation. Materials and Methods: The effects of inoculation by four arbuscular mycorrhizal (AM), fungi, Glomus mossae, Glomus fasciculatum, Gigaspora margarita and Gigaspora gilmorei either alone or supplemented with P-fertilizer, on colchicine concentration in Gloriosa superba were studied. The concentration of colchicine was determined by high-performance thin layer chromatography. Results: The four fungi significantly increased concentration of colchicine in the herb. Although there was significant increase in concentration of colchicine in non-mycorrhizal P-fertilized plants as compared to control, the extent of the increase was less compared to mycorrhizal plants grown with or without P-fertilization. This suggests that the increase in colchicine concentration may not be entirely attributed to enhanced P-nutrition and improved growth. Among the four AM fungi Glomus mossae was found to be best. The total colchicine content of plant (mg / plant) was significantly high in plants inoculated with Glomus mossae and 25 mg kg-1phosphorus fertilizer (348.9 mg /plant) while the control contain least colchicine (177.87 mg / plant).